Immunological Response of Black Bengal Goats to Haemonchus contortus Dominant Acquired Gastrointestinal Nematode Infection - Das, Supradip; Hembram, Ananta; Jas, Ruma; Brahma, Anupam; Kesh, Shyam Sundar; Bera, Santanu (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Goat farming is severely affected by gastrointestinal nematodes (GINs) infection, which is most commonly prevalent and leads to huge production and economic losses. In the present study, total 261 Black Bengal goats, in the age group of 6 months to 2 years, were coprologically screened by flotation technique. The faecal egg count (FEC) per gram (EPG) of faeces was estimated by modified McMaster Technique and pooled faecal samples were cultured to identify dominant GINs. Based on FEC, 90 goats were categorized in to 3 groups; highly infected (EPG > 600), low infected (EPG < 200), non-infected (EPG=0) group and blood samples from selected animals were collected for estimation of haemato-biochemical and immunological parameters. Results revealed that H. contortus was dominant nematode from coproculture with 58% L3 population. The highly infected group had significantly (p